Gender and the digital economy : perspectives from the developing world - Ng, Cecilia, 1950-; Mitter, Swasti, 1939-2016 (SAGE Publications, 2005)
In the global discourse on ICTs, the concern so far has primarily been outsourcing and the loss of service sector jobs from the developed world. This book focuses, instead, on the positive aspects of the digital economy as they relate to women in the developing world. It illustrates--with case studies from Argentina, Morocco, India, Malaysia and the Philippines--how economic empowerment through the medium of ICTs can change the position of women within their families and the workplace, even in the face of uneven development processes. This timely volume, which is rooted in primary and original r.